Slow-release boron fertilizer improves yield and nutritional profile of Beta vulgaris L. grown in Northeast China by increasing boron supply capacity - Wu, Zhenzhen; Zhao, Xiaoyu; Yong, Jean Wan Hong; Sehar, Shafaque; Adil, Muhammad Faheem; Riaz, Muhammad; Verma, Krishan K.; Li, Meiyu; Huo, Jialu; Yang, Songlin; Song, Baiquan (Frontiers in Plant Science, 2024)
The Northeastern part of China is a traditional sugar beet cultivation area where the soils are classified generally as the black and albic soil types with low boron (B) availability. Boron fertilizer can increase soil B content and significantly improve crop yield and quality. At present, the effects of slow-release B fertilizer on beet root yield and quality remained unclear. Two sugar beet varieties KWS1197 and KWS0143 were selected as the research materials; biologically evaluated with three dosage rates of 0, 15, and 30 kg ha -1 in two soil types. Results showed that slow-release B fertilizer 2 (30 kg ha -1 ) improved sugar beet net photosynthetic rate (13.6%) and transpiration rate (9.8%), as well as improving dry matter accumulation and the transfer to underground parts (23.1%) for higher root yield (1.4 to 9.7% in black soil and 3.5-14.2% in albic soil). Specifically, boron fertilizer greatly increased root B accumulation, as evidenced by decreasing amino N and Na contents alongside with increasing surose (Pol) content. Slow-release B fertilizer increased white sugar yield by 3.5 to 35.7% in black soil and 5.8 to 20.8 % in albic soil. In conclusion, applying slow-release B fertilizer is an effective strategy to increase sugar beet yield and quality in Northeast China, with a recommended application rate of 30 kg ha -1 . These findings established a baseline for formulating effective and futristic fertilizer for sugar beet.